PENERAPAN METODE EKSPERENSIAL BERBASIS PROYEK UNTUK MENINGKATKAN RASA CINTA TANAH AIR PADA PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK BAGI SISWA KELAS XII SMK NEGERI PERBATASAN LAMAKNEN SELATAN TAHUN AJARAN 2022/2023 - Suni, Maria Imelda; Usboko, Wilibrordus Cornelis; Mones, Anselmus Yata (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2022)
Love for one's country is one of the main things in forming a citizen's character, namely a sense of belonging, a sense of care, a sense of preserving and a sense of wanting to advance the unity of the nation and state. With this attitude of love, the state of the country will be better. The research objectives are 1) to determine the quality of Catholic Religious Education learning outcomes by applying project-based experiential methods to increase the feeling of love for the country for class 2) to determine the quality of the Catholic Religious Education learning process by applying project-based experiential methods to increase the feeling of love for the country for class This research uses Classroom Action Research (PTK) which consists of Cycle I and Cycle II which has four stages, namely planning, implementation, observation and reflection. The results of the research show that through the application of project-based experiential methods the feeling of patriotism in Catholic Religious Education subjects can increase as follows. The data results for Cycle I were 2.59% and Cycle II were 3.97%. From these data it is concluded that the application of project-based experiential methods can increase the feeling of love for the country in Catholic Religious Education Learning for class.